Unraveling Factors for Gender Discrepancies in Students ' Mathematics Performance in Tanzanian Secondary Schools - Kyaruzi, Florence Kyaruzi (Papers in Education and Development, 2023)
This study investigated the factors leading to gender discrepancies in students ' Mathematics performance and how they could be addressed. Data were collected from 762 Form Four students sampled from 83 public secondary schools in Tanzania and analyzed using descriptive statistics, latent mean analyses and thematic analysis techniques. Quantitative results indicated that students evaluated their Mathematics teachers ' instructional practices positively across gender. Qualitative results showed that students had gendered perceptions toward Mathematics and perceived it as a masculine subject. Further, findings unveiled that students ' masculine orientation toward Mathematics was partly attributed to a biased distribution of domestic chores, social persuasions about girls ' ability in Mathematics and restrictive parenting of girls. Also, the findings indicated that gender discrepancies in Mathematics performance could be addressed by providing gender education to teachers and parents, availing adequate learning resources and creating supportive home learning environments for girls. Based on the findings, practical and theoretical implications are drawn. Keywords: gender discrepancies, mathematics performance, secondary schools, students